Diagnosing the Actual Reality of the Requirements of Ecological Design According to ISO14006:2020: A Case Study in Engineering Reconstruction Office-Iraq - Zainab Mahdi Muhammad; Areej Saeed Khalil (Journal of Techniques, 2022)
The research aims to identify the extent of the commitment of the Department of Engineering Reconstruction to the application of ecological design according to the guiding specification ISO14006:2020 by measuring and diagnosing the gap between the actual reality in the Department of Engineering Reconstruction and the requirements of the specification, and to achieve this goal, the case study approach was adopted, and the checklist was adopted to measure the gap. Methodology: The study starts from the problem represented by the gap between the actual reality of ecological design in the Department of Engineering Reconstruction and Ecodesign by the requirements of ISO 14006:2020. Prepared by the British Standards Organization (BSI). Results: The results of the research show that the total rate achieved by measuring the availability of eco-design requirements in the Department of Engineering Reconstruction according to ISO14006:2020 obtained a percentage of (75%) and an implementation rate of (5), meaning that it is close to a fully documented application, which generated a gap of (24%). The research came out with conclusions, the most prominent of which is that although the research organization understands design and development when integrating eco-design into design and development, it does not have documented information in this regard. Some internal problems in the documentation of some requirements of the standard.